Financial Constraints, Intangible Assets, and Firm Dynamics : Theory and Evidence - Chen, Sophia (Washington, D.C. : International Monetary Fund, 2014)
I study whether firms' reliance on intangible assets is an important determinant of financing constraints. I construct new measures of firm-level physical and intangible assets using accounting information on U.S. public firms. I find that firms with a higher share of intangible assets in total assets start smaller, grow faster, and have higher Tobin's q. Asset tangibility predicts firm dynamics and Tobin's q up to 30 years but has diminishing predicative power. I develop a model of endogenous financial constraints in which firm size and value are limited by the enforceability of financial contracts. Asset tangibility matters because physical and intangible assets differ in their residual value when the contract is repudiated. This mechanism is qualitatively important to explain stylized facts of firm dynamics and Tobin's q.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet